2018
DOI: 10.1097/mnm.0000000000000779
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of biological and clinical aggressiveness of invasive ductal breast cancer using baseline 18F-FDG PET/CT-derived volumetric parameters

Abstract: SUVmax may appropriately reflect the immunohistochemical characteristics of IDBC, whereas TLG is associated with clinical risk factors and systemic metastasis. Our preliminary findings suggesting different relationships between volumetric parameters and the clinical tumor size and the Ki-67 index for different subtypes require further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 36 publications
3
17
4
Order By: Relevance
“…In previous studies on breast cancer patients, although volumetric parameters of [ 18 F]FDG PET/CT cannot be used to differentiate hormone receptor status of cancer, TLG was significantly associated with aggressive tumor features and the presence of systemic metastasis [11][12][13]. In addition, TLG was a significant predictor for disease-free survival and overall survival in breast cancer patients [11][12][13]. Therefore, it was expected that TLG had significant associations with both RFS and distant RFS in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies on breast cancer patients, although volumetric parameters of [ 18 F]FDG PET/CT cannot be used to differentiate hormone receptor status of cancer, TLG was significantly associated with aggressive tumor features and the presence of systemic metastasis [11][12][13]. In addition, TLG was a significant predictor for disease-free survival and overall survival in breast cancer patients [11][12][13]. Therefore, it was expected that TLG had significant associations with both RFS and distant RFS in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…2-Deoxy-2-[ 18 F]fluoro-D-glucose ([ 18 F]FDG) positron emission tomography/computed tomography (PET/CT) has significant prognostic potential for predicting clinical outcomes in patients with breast cancer [11,12]. Maximum [ 18 F]FDG uptake of primary tumor has been the most commonly used predictive parameter of PET/CT; however, recent studies have reported that volumetric PET/CT parameters such as metabolic tumor volume (MTV) and total lesion glycolysis (TLG) have more significant association with survival than maximum [ 18 F]FDG uptake in breast cancer [11][12][13]. In addition to the assessment of primary tumor features, a number of recent studies have demonstrated that the degree of systemic inflammatory response to malignancy can be evaluated with [ 18 F]FDG PET/CT by measuring [ 18 F]FDG uptake of bone marrow (BM) [14,15].…”
mentioning
confidence: 99%
“…Duplicate articles, review articles, case reports, non-English publications, and articles, which not contain correlation coefficients between PET and Ki-67 were excluded (n= 1568). Therefore, the present analysis comprises 32 studies with 1801 patients ( Table 1 ) [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] . The following data were extracted from the literature: authors, year of publication, number of patients, histopathological parameters, and correlation coefficients.…”
Section: Methodsmentioning
confidence: 99%
“… 40 different 18 F-FDG Contractor et al [21] 2011 United Kingdom prospective n.r. 18 different 18 F-FLT Crippa et al [22] 2015 Italy prospective different 15 different, none triple negative 18 F-FLT De Cremoux et al [23] 2018 France retrospective different 75 Luminal types 18 F-FDG Ege Aktas et al [24] 2017 Turkey retrospective IDC 65 different 18 F-FDG Garcia Vicente et al [26] 2012 Spain prospective different 68 different 18 F-FDG García-Esquinas et al [25] 2014 Spain prospective n.r. 43 different 18 F-FDG Groheux et al [27] 2018 France prospective different 55 Triple negative 18 F-FDG Humbert et al [28] 2014 France prospective different 61 Luminal types 18 F-FDG Ikenaga et al [29] 2007 Japan retrospective different 45 different 18 ...…”
Section: Methodsmentioning
confidence: 99%
“…There is interest in using 18 F-FDG PET/CT to quickly assess tumor responses to therapy, and the fact that PET may identify patients that respond to treatment is attractive for personalized health care (16). A baseline PET scan prior to and following 1 or 2 cycles of treatment may be used to confirm effective treatment for that specific tumor and patient (21). Rapid readouts of the effect of treatment and prompt patient shifting to more suitable therapy types for that particular patient could save money, time and preserve the patient's health (12,16).…”
Section: Discussionmentioning
confidence: 99%